The Black Church in the African American Experience - Lincoln, C. Eric (Charles Eric), 1924-2000 (Book collections on Project MUSE., 1990)
Black churches in America have long been recognized as the most independent, stable, and dominant institutions in black communities. In The Black Church in the African American Experience, based on a ten-year study, is the largest nongovernmental study of urban and rural churches ever undertaken and the first major field study on the subject since the 1930s. Drawing on interviews with more than 1,800 black clergy in both urban and rural settings, combined with a comprehensive historical overview of seven mainline black denominations, C. Eric Lincoln and Lawrence H. Mamiya present an analysis of.